Definition af kompetenceniveauer i fremmedsprog inden for en fælles europæisk referenceramme - Lauridsen, Karen (HERMES - Journal of Language and Communication in Business, 2003)
The definition of levels of foreign language competence is anything but unambiguous. There is thus a need for a more fine-tuned framework of reference, within which the different levels of competence may be described. In this article the Common European Framework of Reference, developed under the auspices of the Council of Europe, will be briefly described as will DIALANG, a web-based diagnostic testing system developed in accordance with the common European framework. Finally, the strengths and weak-nesses as well as the perspectives for future use of these new tools will be discussed.